One-step synthesis of ordered mesoporous CoAl2O4 spinel-based metal oxides for CO2 reforming of CH41. Issue 60 (2nd July 2015) - Xu, Leilei; Zhang, Jian; Wang, Fagen; Yuan, Kaidi; Wang, Liangjun; Wu, Kai; Xu, Guoqin; Chen, Wei
<x xml:space="preserve">Abstract</x> Ordered mesoporous CoAl2O4 spinel-based metal oxides were facilely synthesized and utilized as the catalysts for CRM reactions.